2023
DOI: 10.3390/genes14040870
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the SHI-Related Sequence Family in Cassava

Abstract: The SHORT INTERNODES (SHI)-related sequences (SRS) are plant-specific transcription factors that have been quantitatively characterized during plant growth, regeneration, and stress responses. However, the genome-wide discovery of SRS family genes and their involvement in abiotic stress-related activities in cassava have not been documented. A genome-wide search strategy was used to identify eight family members of the SRS gene family in cassava (Manihot esculenta Crantz). Based on their evolutionary linkages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Additionally, some BnSRS genes contained stress-responsive, drought-inducibility, cell cycle regulation, and other related elements in the promoter region (Figure 6). These results suggest that BnSRS genes may play a crucial role in regulating hormone responses and in response to stresses, as well as growth and development, which is consistent with the SRS gene family in Cassava [61] and cotton [8].…”
Section: Analysis Of Cis-acting Elements Of the Bnsrs Genessupporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, some BnSRS genes contained stress-responsive, drought-inducibility, cell cycle regulation, and other related elements in the promoter region (Figure 6). These results suggest that BnSRS genes may play a crucial role in regulating hormone responses and in response to stresses, as well as growth and development, which is consistent with the SRS gene family in Cassava [61] and cotton [8].…”
Section: Analysis Of Cis-acting Elements Of the Bnsrs Genessupporting
confidence: 79%
“…Only the expression of BnSRS18 showed a significant increase, with a nearly 2-fold up-regulation, while the expression of BnSRS21 showed a substantial decrease, with a nearly 3-fold down-regulation (Figure 8B). These results suggested that the BnSRS genes play an important role in response to a variety of stresses, as in other species [6][7][8][9]61].…”
Section: Expression Pattern Analysis Of Bnsrs Gene Family Membersmentioning
confidence: 69%
See 1 more Smart Citation